1990
DOI: 10.1002/art.1780330103
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serologic indicators of inflammation with effectiveness of nonsteroidal antiinflammatory drug therapy in rheumatoid arthritis

Abstract: Forty-seven patients with rheumatoid arthritis (mean duration 5.7 years) who were receiving neither disease-modifying drugs nor corticosteroids were enrolled in a 12-week, multicenter study of the relationship between clinical and serologic measures of disease activity in patients taking nonsteroidal antiinflammatory drugs. After a 2-week drug washout period, patients received flurbiprofen (200 mg/day) or sustained-release ibuprofen (2,400 mg/day) for a 10-week trial. Clinical response was assessed biweekly us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…A study by Cush et al showed a positive effect of NSAIDs on disease activity. 31 In contrast with others we found a relation between renal function and good response. The response was better in patients with a lower creatinine clearance.…”
Section: Discussioncontrasting
confidence: 99%
“…A study by Cush et al showed a positive effect of NSAIDs on disease activity. 31 In contrast with others we found a relation between renal function and good response. The response was better in patients with a lower creatinine clearance.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the fact that the erythematous reaction was only partially inhibited by ibuprofen (20%) suggests the vascular changes induced by urate crystals are only partly due to prostaglandins via activation of cyclo-oxygenase. Our data provide indirect evidence suggesting that differences in biochemical determinants of inflammation between subjects may explain variability in response to NSAIDs [11].…”
Section: Resultsmentioning
confidence: 66%
“…Failure to obtain relief with one drug usually leads to a rotation through a series of drugs until a satisfactory response is obtained [5]. Significant between-subject variation has been noted in several studies [4,5,[6][7][8][9][10][11]. The basis for this is unknown but it has been suggested that this variability could be either pharmacokinetic and/or pharmacodynamic in origin.…”
Section: Introductionmentioning
confidence: 99%
“…These correlations, however, were less striking than those between more traditional measures of disease activity (14). These findings tend to discourage the clinical application of cICAM-1 determinations as a gauge of clinical activity in RA.…”
Section: Discussionmentioning
confidence: 69%
“…Correlation of cICAM-1 with disease activity. Serum samples were collected from 25 RA patients who participated in a 12-week NSAID protocol (14,15). Serum cICAM-1 levels were compared with a variety of clinical variables and measures of disease activity.…”
Section: Resultsmentioning
confidence: 99%